A Comparative Analysis of the Land Policies of Umar bin Khattab and the 1960 Basic Agrarian Law - Salma, Kholidiyah; Sj, Fadil (Tebuireng: Journal of Islamic Studies and Society, 2025)
Fair land management constitutes one of the pillars of social welfare. In Islamic history, Caliph Umar ibn al-Khattab is well known for his land policies, which emphasized the social function of land, the prohibition of land abandonment, and equitable distribution. Meanwhile, Indonesia has the Basic Agrarian Law (Undang-Undang Pokok Agraria/UUPA) of 1960 as the foundation of its national agrarian law, regulating land tenure, utilization, and registration. This study aims to conduct a comparative analysis of Umar ibn al-Khattab’s land policies and the provisions of the UUPA in order to identify the similarities and differences in the principles governing both systems. The research method employed is a literature review using a normative–historical approach. Data sources include classical Islamic literature, historical chronicles, fiqh books, the 1960 Basic Agrarian Law, and relevant prior studies. The findings indicate points of convergence between Umar’s policies and the UUPA, particularly regarding the principle of the social function of land, the principle of equitable distribution, and the prohibition of ownership monopolies. The differences lie in institutional aspects and legal procedures: Umar’s policies were contextual ijtihad, whereas the UUPA is a codified legal product with formal administrative mechanisms. The contribution of this study is to offer an Islamic historical perspective as an ethical foundation for the refinement of national agrarian law toward the realization of social justice.